2022
DOI: 10.1021/acs.iecr.2c00370
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@MoS2/rGO Nanocomposite/Ionic Liquid Modified Carbon Paste Electrode for Electrochemical Sensing of Dasatinib in the Presence of Doxorubicin

Abstract: Cancer treatment by chemotherapy exploits one or more anticancer drugs to kill cancer cells. Because of the various side effects of chemotherapy drugs, sensitive determination of these drugs is one of the greatest challenges of adjuvant therapy. This study introduced the preparation of a selective and sensitive electrochemical sensor based on a carbon paste electrode (CPE) modified with Fe 3 O 4 @MoS 2 /reduced graphene oxide nanocomposite and ionic liquid (IL) (Fe 3 O 4 @MoS 2 /rGO/ILCPE) to determine dasatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 60 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Moreover, monitoring glucose is also highly important in pharmaceutical products where several food products are being used [ 6 ]. Until now, metal oxides (MOs) and metal sulfides (MSs) have been used as advanced electrocatalysts for developing highly sensitive electrochemical sensors [ 7 , 8 , 9 ]. However, these sensors have drawbacks such as low detection limits [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, monitoring glucose is also highly important in pharmaceutical products where several food products are being used [ 6 ]. Until now, metal oxides (MOs) and metal sulfides (MSs) have been used as advanced electrocatalysts for developing highly sensitive electrochemical sensors [ 7 , 8 , 9 ]. However, these sensors have drawbacks such as low detection limits [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our research, only a few articles have reported on the electrochemical measurement of DOX and DAS simultaneously. , Previous reported research showed that DAS and DOX are electroactive anticancer agents possessing high overvoltage potential, which could be detected via electrochemical sensors. A poor oxidation signal and high overpotential make it difficult to determine the low levels of these anticancer agents. Accordingly, the modification of an electrode surface is essential to analyze the low concentrations of studied anticancer agents.…”
Section: Introductionmentioning
confidence: 92%
“…There is a broad field of application of room temperature ionic liquids (RTILs) in analytical chemistry. RTILs are mixed with carbon substances to construct the conductive composites applied in electrochemical structures due to advantages such as a low vapor pressure, high conductivity, a wide electrochemical window, satisfactory chemical–thermal stability, and negligible toxicity [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%